SCOPING REVIEW: IDENTIFIKASI JENIS INTERVENSI GABUNGAN DALAM UPAYA PENANGGULANGAN LEPTOSPIROSIS DI WILAYAH JAWA TENGAH BAGIAN SELATAN - Intansari, Fety Fatima; Adi, Mateus Sakundarno; Udijono, Ari; Saraswati, Lintang Dian (Jurnal Kesehatan Masyarakat (Undip), 2022)
This study aims to describe the strategy of strengthening the intervention that has been used in the form of using a combined intervention in an effort to control leptospirosis in the Southern part of Central Java Province. Scoping Review procedure was used on 4 databases (SCOPUS, JSTOR, Garuda, and gray literature on Google Scholar). The purpose of this study was to describe strategies to strengthen interventions that have been used as a combination in efforts to control leptospirosis in the Southern part of Central Java Province. The results of this study found that as many as 6 articles combined health education interventions with other interventions such as screening interventions in the form of live trapp installation, application training, accompanied by the provision and assistance of PPE, training of laboratory personnel, field observations, risk factor surveys, and environmental observations. The combination of this type of leptospirosis intervention is also able to increase the knowledge value of correspondents related to leptospirosis disease.